EFFECT OF MINERAL FILLER TYPE AND CONTENT ON PROPERTIES OF ASPHALT CONCRETE MIXES (Journal of Engineering, 2010)
Some of the newly constructed highway pavements in Iraq have shown premature failures with consequential negative impacts on both roadway safety and economy. Major types of these failures are permanent deformation (rutting) and cracking. Fillers were suspected to be a major contributor to these failures. The objective of this study is to evaluate the influence of new different fillers extracted from different local sources on the performance of asphalt mixtures. The effect of filler type and content on the failures potential of asphalt concrete as well as other mixes properties was investigated. A detailed laboratory study is carried out by preparing asphalt mixtures specimens using aggregate from Al-Taji quarry, (40-50) grade asphalt from dourah refinery and three different types of fillers (Portland cement, Silica fume, and Fly ash) were tested in the laboratory. Marshal Mix design was made using all types of fillers and different ratios to evaluate the performance of different types and filler quantities in the asphalt mixture. The mechanical properties of mixes were studied using indirect tensile strength, creep and marshal tests. Three different tests temperature (15,30,45C°) were employed in the indirect tensile test to investigate the susceptibility of these mixes to change in temperature. Results of this study indicate that replacement of Portland cement by 9.8% of silica fume aggravates resistance of the mixes to rutting and cracking. Furthermore, coal fly ash cannot be used as mineral filler in hot mix asphalt paving applications.